La producción avícola en la parroquia Cotaló y los efectos en las ventas tras el rebrote de la gripe aviar en el año 2022 - Mariela Hidalgo (2024)
ABSTRACT: The main objective of this research work was to determine the poultry production in Cotaló parish and the effects on sales after the outbreak of avian flu in the year 2022, through the diagnosis of poultry production levels, the comparison of the sales index of products and finally with the proposal of production strategies to improve sales of poultry in the parish taking into account that the poultry activity in Cotaló parish is the main source of income and the largest generator of employment in the parish. The hypothetical deductive method was used since it was based on a hypothesis, after that, surveys and interviews were conducted, which were analyzed using SPSS for the surveys and the analysis through the type of interview used in this research work, which was the structured interview since 7 questions were structured, fixed and sequential, to a specific group of people. Finally, the following results were obtained: poultry production in Cotaló parish is approximately 85,000 eggs per day and the effect is that sales have increased since no contagions have been recorded in the parish; however, it was affected for a short period of time due to external factors such as the war between Ukraine and Russia, since that is where the raw material comes from. Keywords: Poultry, sale, production, employment, and flu aviary